2010
DOI: 10.1111/j.1467-9604.2010.01461.x
|View full text |Cite
|
Sign up to set email alerts
|

The transformative nature of the special school placement: reporting ‘insistent’ data from emerging teachers and exploring an agenda for future research

Abstract: Emerging teachers undergoing initial teacher education programmes and given the opportunity to engage in a teaching placement in special provisions settings consistently report that they find the experience transformative. Over eight years, informal and often unprompted data emerged which ‘insisted’ upon reporting and suggested that the special school placement was transformative and differed in some significant features from other placements. There are themes of emerging teachers’ confidence in their ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In relation to the educational system, there are five significant implementation issues: (1) postprimary teacher trainees did not have any formal education training of students with SEN (training modules only included in 2012); (2) assessment of special educational need is by diagnosis of disability followed by assessment of SEN that arises from this disability; (3) difficulties in accessing educational psychologist assessments and the excessive delays and concerns over the quality of the reports (Kenny et al., , Irish National Teachers' Organisation, ); (4) special schools follow the national primary school guidelines, even for students aged 12+, which could limit full access to postprimary curriculum options; and (5) there are cultural and educational differences between primary and postprimary education (Smyth, ) and between mainstream and special educational school environment (Feeney, Gager, & Hallett, ).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the educational system, there are five significant implementation issues: (1) postprimary teacher trainees did not have any formal education training of students with SEN (training modules only included in 2012); (2) assessment of special educational need is by diagnosis of disability followed by assessment of SEN that arises from this disability; (3) difficulties in accessing educational psychologist assessments and the excessive delays and concerns over the quality of the reports (Kenny et al., , Irish National Teachers' Organisation, ); (4) special schools follow the national primary school guidelines, even for students aged 12+, which could limit full access to postprimary curriculum options; and (5) there are cultural and educational differences between primary and postprimary education (Smyth, ) and between mainstream and special educational school environment (Feeney, Gager, & Hallett, ).…”
Section: Introductionmentioning
confidence: 99%
“…A follow-up study (Feeney et al, 2010), which gathered data on pre-service teachers who underwent a practicum in a special education school in England over a period of eight years, found that the pre-service teachers identified changes in their professional identity, their stances and teaching skills.…”
Section: Practicum In Special Educationmentioning
confidence: 99%